FEN BİLGİSİ ÖĞRETMEN ADAYLARININ GDO'LU BESİNLERLE İLGİLİ RİSK ALGILARININ İNCELENMESİ. - DEMİRAL, Ümit; TÜRKMENOĞLU, Hande (Electronic Turkish Studies)
The aim of this study is to investigate the risk perceptions of preservice science teachers in terms of some factors in a socio-scientific context like food with GMOs. In this study, one of the quantitative research methods, the survey model was used. The sample of the research consists of a total of 255; 1st, 2nd, 3rd and 4th grade preservice science teachers in Ahi Evran University, Science Education Department. The Personal Information Scale and the Risk Perception Scale for Foods with GMOs were used as data collection tools in the study. During the analysis of the data obtained from the scales; frequency (f), percent (%), mean ( ) and standard deviation (SD) values were used as descriptive statistics and Kruskal Wallis and Mann-Whitney U tests were used for explanatory statistical techniques. In the findings, it was determined that preservice science teachers' risk perceptions for GMOs were above the medium level. When examined in terms of variables, it was found that the risk perceptions of female preservice teachers were significantly higher than those of male preservice teachers. It was found that preservice teachers who are studying in the last grade have significantly higher risk perceptions than preservice teachers who are studying in other classes. On the other hand, no significant difference was found between female and male preservice teachers in terms of academic grade point average, character trait, parental education status and settlement place. The fact that preservice science teachers' risk perceptions are above the average is thought to be the impact of mass media. It is also thought that because of the social roles and daily activities based on the gender difference, the risk perceptions of female preservice teachers are higher than that of the males. The lessons that the senior preservice teachers have taken during the undergraduate period may have an impact for the senior preservice teachers' low level of risk perceptions compared to other classes. Based on the results of the research, suggestions have been made to the undergraduate science teacher education program and researchers.